Residual inflammatory risk and vulnerable plaque in the carotid artery in patients with ischemic stroke - Gong, Xiuqun; Yu, Chuanqing; Lu, Zeyu; Wang, Xia; Cai, Qiankun; Cheng, Xiaosi; Lu, Jun (Frontiers in Neurology, 2024)
Objective: Inflammation is a central driver of atherogenesis and eventual plaque rupture. This study aimed to evaluate the association between residual inflammatory risk (RIR) and vulnerable plaque in the carotid artery in patients with ischemic stroke.: Patients with acute ischemic stroke were enrolled from January 2021 to July 2022. They were divided into four groups: RIR only (LDL-C <2.6 mmol/L and hsCRP ≥2 mg/L), residual cholesterol risk (RCR) only (LDL-C ≥2.6 mmol/L and hsCRP <2 mg/L), both risk or residual cholesterol and inflammatory risk (RCIR) (LDL-C ≥2.6 mmol/L and hsCRP ≥2 mg/L), and neither risk (LDL-C <2.6 mmol/L and hsCRP <2 mg/L). Vulnerable plaque was determined if low attenuated plaques CT value < 35 Hounsfield Units (HU) and remodeling index > 1.1 which indicated a positive remodeling.